Research on Radio Resource Management for Hierarchical Heterogeneous Wireless Network - Feng Tian; Hantao Liu; Liang Zhou (Dianxin kexue)
With the development of communication technology, the hierarchical heterogeneous characters of coverage in networks become more and more clear, which is caused by the need of high quality for wireless applications to users. By the exploration of the radio resource management for heterogeneous hierarchical wireless network, the key techniques were demonstrated which could significantly improve the transmission rate and reduce the energy cost.